Optimization of Gantry Cranes’ Operation Path for Transshipment Based on Improved TSP - Qi Zhang; Hongjin Dong; Mingjun Ling; Leyi Duan; Yuguang Wei (Journal of Advanced Transportation)
In order to improve the transshipment efficiency of transit containers in the port or the port-type railway network container freight station (PRNCS) with the condition that each transit container matches a railway flat-car, this paper studied the optimization of operation path of the rail mounted gantry crane (RMG) in the loading and unloading track for containers transshipped directly from highway to railway. Based on the basic model of TSP, the paper constructed the optimization model for the operation path of RMG, and designed the Ant Colony Algorithm (ACA) to solve it, and then obtained the operation scheme of RMG having the highest efficiency. Finally, the validity and correctness of the model and algorithm were verified by a case.